Sistema integrado para geolocalização e rastreamento - Parisoto, Wagner (2015)
This work Completion of course, presents the approach used for the development of a client-server system that supports geolocation and tracking of people through mobile devices. The system when installed on the mobile device of a person, allows through some mechanism, such as artificial satellites, capturing its location anywhere on the earth and then through a connection to the Internet, send data to a remote server, thus allowing real-time monitoring of the person and also your location history.